W sprawie definicji idiomu - Zakrzewski, Paweł (Acta Universitatis Lodziensis. Folia Linguistica, 2002)
In the paper About the definition of idiom, there is a kind of comparison between the definitions of idiom of different authors, drawn in order to provide a common and coherent definition. Thus, idiom is an untranslatable connection of at least two words, not being a sentence, where there are semantic changes as far as the primitive meanings of the components are concerned. In addition, a sort of division of idioms into two categories is proposed; a distinction is made between nominal and verbal idioms.